Portraits of Science Misconceptions in Plant Adaptation and Breeding Materials in Elementary Schools - Candra Utama; Anisa Wahyu Kusumaningtyas (Universitas Pendidikan Ganesha, 2023)
A misconception is a misunderstanding of a concept by someone. Misconceptions can be experienced in various situations, one of which is in the learning process. This research takes the learning in elementary schools, especially on plant adaptation and reproduction. Misconception itself occurs due to many factors. This study aimed to determine whether there were misconceptions about plant adaptation and reproduction in the elementary schools studied. The researcher used a descriptive qualitative approach. This type of qualitative research uses a descriptive approach. The population in this study amounted to 47 students. Sampling was done using probability sampling. Data collection techniques used were tests and interviews. The test instrument used is to give 15 question numbers to students. The data analysis technique used is descriptive qualitative analysis. The study results showed that 19% of the samples had misconceptions about vegetative propagation of plants, 13% of generative plant propagation, and 2% of plant adaptation material. The teacher also explained that only a few students needed clarification, and the rest needed help understanding the concept. There are many ways to overcome misconceptions, starting from learning media, using worksheets, developing critical thinking in students, and many more. It was concluded that elementary school students have misconceptions.